Trade-offs in resource allocation in the intracellular life-cycle of hepatitis C virus - McLean, Alison K.; Luciani, Fabio; Tanaka, Mark M. (Journal of theoretical biology, 2010)
Positive sense single-stranded RNA viruses undergo three mutually exclusive processes to replicate within a cell. These are translation to produce proteins, replication to produce RNA viral genomes, and packaging to form virions. The allocation of newly synthesised viral genomes to these processes, which can be regarded as life-history traits, may be subject to natural selection for efficient reproduction. Here, we develop a mathematical model of the process of intracellular viral replication to study alternative strategies for the allocation and reallocation of viral genomes to these processes. We explore four cases of the model: (1) Free Movement, in which viral genomes can freely be allocated and reallocated among translation, replication and packaging; (2) Unidirectional Reallocation, in which allocation occurs freely but reallocation can only proceed from translation to replication to packaging; (3) Conveyor Belt, in which viral genomes are first allocated to translation, then passed on to replication and finally to packaging; and (4) Permanent Allocation in which new genomes are allocated to the three processes but not reallocated between them. We apply this model to hepatitis C virus and study changes in the production of virus as the rates of allocation and reallocation are varied. We find that high viral production occurs when allocation and reallocation of the genome are weighted towards the translation and replication processes. The replication process in particular is favoured. The most productive strategy is a form of the Free Movement model in which genomes are allocated entirely to the replication–translation cycle while allowing some genomes to be packaged through reallocation.